Polyadenylated, noncapped RNA from the archaebacterium Methanococcus vannielii. - Brown, J W (1985)
Polyadenylated [poly(A)+] RNA molecules have been isolated from Methanococcus vannielii by oligodeoxythymidylate-cellulose affinity chromatography at 4 degrees C. Approximately 16% of the label in RNA isolated from cultures allowed to incorporate [3H]uridine for 3 min at 37 degrees C was poly(A)+ RNA. In contrast, less than 1% of the radioactivity in RNA labeled over a period of several generations was contained in poly(A)+ RNA molecules. Electrophoretic separation of poly(A)+ RNA molecules showed a heterogeneous population with mobilities indicative of sizes ranging from 900 to 3,000 bases in length. The population of poly(A)+ RNA molecules was found to have a half-life in vivo of approximately 12 min. Polyadenylate [poly(A)] tracts were isolated by digestion with RNase A and RNase T1 after 3' end labeling of the poly(A)+ RNA with RNA ligase. These radioactively labeled poly(A) oligonucleotides were shown by electrophoresis through DNA sequencing gels to average 10 bases in length, with major components of 5, 9, 10, 11, and 12 bases. The lengths of these poly(A) sequences are in agreement with estimates obtained from RNase A and RNase T1 digestions of [3H]adenine-labeled poly(A)+ RNA molecules. Poly(A)+ RNA molecules from M. vannielii were labeled at their 5' termini with T4 polynucleotide kinase after dephosphorylation with calf intestine alkaline phosphatase. Pretreatment of the RNA molecules with tobacco acid pyrophosphatase did not increase the amount of phosphate incorporated into poly(A)+ RNA molecules by polynucleotide kinase, indicating that the poly(A)+ RNA molecules did not have modified bases (caps) at their 5' termini. The relatively short poly(A) tracts, the lack of 5' cap structures, and the instability of the poly(A)+ RNA molecules isolated from M. vannielii indicate that these archaebacterial poly(A)+ RNAs more closely resemble eubacterial mRNAs than eucaryotic mRNAs.